2016
DOI: 10.1016/j.stem.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The Central Nervous System Regulates Embryonic HSPC Production via Stress-Responsive Glucocorticoid Receptor Signaling

Abstract: Summary Hematopoietic stem and progenitor cell (HSPC) specification is regulated by numerous defined factors acting locally within the hemogenic niche, however, it is unclear whether production can adapt to fluctuating systemic needs. Here, we show the central nervous system controls embryonic HSPC production via the hypothalamic-pituitary-adrenal/interrenal (HPA/I) stress response axis. Exposure to serotonin or the reuptake inhibitor fluoxetine increased runx1 expression and Flk1+/cMyb+ HSPCs, independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 39 publications
4
57
0
Order By: Relevance
“…Administration of the antidepressant fluoxetine as well as social interactions were shown to restore normal behavior [75,77]. Using this mutant, it was demonstrated that Gr mediates the glucocorticoid-induced inhibition of leukocyte migration upon wounding [78] and the stimulation of the formation of hematopoietic stem and progenitor cells (HSPCs) by glucocorticoids [79]. In addition, it was found that light adaptation in the retina was disturbed in mutant larvae [80].…”
Section: The Zebrafish Grmentioning
confidence: 99%
“…Administration of the antidepressant fluoxetine as well as social interactions were shown to restore normal behavior [75,77]. Using this mutant, it was demonstrated that Gr mediates the glucocorticoid-induced inhibition of leukocyte migration upon wounding [78] and the stimulation of the formation of hematopoietic stem and progenitor cells (HSPCs) by glucocorticoids [79]. In addition, it was found that light adaptation in the retina was disturbed in mutant larvae [80].…”
Section: The Zebrafish Grmentioning
confidence: 99%
“…Just as neurons process stimuli coming from outside the CNS, neuronal activity also initiates, controls or regulates events occurring outside the CNS. North and colleagues investigated central regulatory mechanisms in hematopoietic stem (HPS) cell production during the embryonic development of zebrafish (22). Generally, the formation and maintenance of HPS cells are characterized by precisely tuned mechanisms that bring together various cellular signals and result in a balance of HPS cell selfrenewal and differentiation.…”
mentioning
confidence: 99%
“…However, some signals travel long distances through the circulation to regulate blood cell formation. In this issue, Kwan et al (Kwan et al, 2016) report that a pathway activated by stress in the brain promotes hematopoietic stem and progenitor cell (HSPC) formation at a distance in the dorsal aorta of zebrafish embryos.…”
mentioning
confidence: 99%
“…In this issue, Kwan et al (Kwan et al, 2016) determine the mechanism by which one of these regulators, serotonin, enhances HSPC formation. Serotonin is a monoamine derived from tryptophan.…”
mentioning
confidence: 99%
See 1 more Smart Citation